Evaluasi Karakteristik Campuran AC-BC menggunakan Abu Cangkang Kemiri sebagai Bahan Substiusi Filler terhadap Parameter Marshall - Kusmira Agustian; Roni Agusmaniza; Syaifuddin Syaifuddin (Portal: Jurnal Teknik Sipil, 2021)
The quality of the asphalt mixture was influenced by using the type and arrangement of aggregate, asphalt and, filler. Filler Stone ash, fly ash is commonly used in asphalt mixtures. However, these fillers are hard to find and not cheap. Candlenut shell ash (CSA) is expected to be an alternative. This research was conduct to evaluate the effect of using CSA as filler substitution on Marshall characteristics of the AC-BC mixture. The research method begins with making test samples with variations in asphalt percentage to obtain optimum asphalt content for each percentage of CSA substitution to the weight of filler in the mixture, which is 0%, 10%, and 20%. Research results show that the highest stability value is obtained when using 20% CSA, which is 2,373.06 kg. The increase of the percentage of CSA in the asphalt mixture causes the VIM and flow values to decrease, while the VFA and MQ increase. density and VMA values did not change significantly. The highest durability value was obtained at 20% CSA, which was 101.8%.